2020
DOI: 10.1111/gcb.14961
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the potential effects of land‐use and climate change on stream conditions

Abstract: Land‐use and climate change are significantly affecting stream ecosystems, yet understanding of their long‐term impacts is hindered by the few studies that have simultaneously investigated their interaction and high variability among future projections. We modeled possible effects of a suite of 2030, 2060, and 2090 land‐use and climate scenarios on the condition of 70,772 small streams in the Chesapeake Bay watershed, United States. The Chesapeake Basin‐wide Index of Biotic Integrity, a benthic macroinvertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
(108 reference statements)
0
13
0
Order By: Relevance
“…The quadrant and individual-projection approaches capture uncertainty stemming from GCMs and RCPs without differentiating between the two sources, which is useful for the scenario planning context focused on capturing the broadest range of plausible conditions. Treating this uncertainty together has precedent in the literature (Battaglin et al 2020;BOR 2014;Hay and McCabe 2019;Maloney et al 2020).…”
Section: Generating Climate Futuresmentioning
confidence: 99%
“…The quadrant and individual-projection approaches capture uncertainty stemming from GCMs and RCPs without differentiating between the two sources, which is useful for the scenario planning context focused on capturing the broadest range of plausible conditions. Treating this uncertainty together has precedent in the literature (Battaglin et al 2020;BOR 2014;Hay and McCabe 2019;Maloney et al 2020).…”
Section: Generating Climate Futuresmentioning
confidence: 99%
“…We had no a priori reason to select any bioregion as a baseline and thus used Blue Ridge (BR) as the default (alphabetically first) contrast for Bioregion in the model. Selected landscape predictors were identified in previous studies to be important drivers of stream condition (Hill et al 2017 ) and the Chessie BIBI (Maloney et al 2018 ; Maloney et al 2020 ). Exploratory model testing found that incorporating nonlinear effects did not improve the ability to accurately predict Chessie BIBI scores in a validation dataset (Table S3 ); therefore, we built a single logistic regression model that included only linear effects (glm function in R with a binomial logit link function).…”
Section: Methodsmentioning
confidence: 99%
“…We used this dataset to examine the likelihood of a degraded stream condition in a flow-altered site for both the observed (Eng et al 2019 ) and our modeled estimates of flow-alteration class (altered, unaltered) for each of the 12 HMs using contingency tables (flow-alteration class × stream condition) and Fisher’s Exact Tests for significant odds ratios as specified above. Limited sample size and lack of samples in each bioregion (Table S4 ), given its importance in previous studies (Maloney et al 2018 , 2020 ), precluded use of a logistic regression model.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To predict the flow metrics for the end‐of‐century time period, the random forest model was applied with the same static predictors, but with the end‐of‐century precipitation data for the wet, dry and moderate periods. Some static variables like land cover change can impact stream habitat (Maloney et al, 2020); however, because our region includes only the unaltered watersheds predominantly in mountainous areas, many of which are protected, we do not anticipate substantial urbanization in future years. All processing for the streamflow metrics was completed in R (R Core Team, 2018).…”
Section: Methodsmentioning
confidence: 99%